Naked on the Deserts of Mars. Issue 3 (January 2016) - Reger, Gary
Abstract : When John Carter, hero of Edgar Rice Burroughs's Princess of Mars, arrives on the Red Planet, he finds himself and all its inhabitants naked. In this paper, I place this trope of nudity into its contemporary social and cultural context and explore the multiple arenas within which it may have operated on its contemporary readers. Much more than simple titillation, depictions of public nudity in the later nineteenth- and early twentieth-century western imagination resonates in a complex and tense universe where barbarity, innocence, Edenic fantasies, and the American west collided, a space in which Richard Slotkin's "man who knows Indians" comes to the fore with adaptive advantages that enable Carter to rise to Martian leadership—but also make him ultimately unsuited for decent society back home on Earth.